The Effect of Dopamine Antagonist Treatment on Auditory Verbal Hallucinations in Healthy Individuals Is Clearly Influenced by COMT Genotype and Accompanied by Corresponding Brain Structural and Functional Alterations: An Artificially Controlled Pilot Study - Zhuo, Chuanjun; Xu, Yong; Zhang, Li; Jing, Rixing; Zhou, Chunhua (Frontiers in Genetics, 2019)
Few studies have been conducted to explore the influence of the COMT genotype on the severity and treatment effect of auditory verbal hallucinations symptoms (AVHs) in healthy individuals with AVHs (H-AVHs) subjects. We hypothesized that the effect of dopamine antagonist treatment on AVHs in H-AVHs may be influenced by their catechol-o-methyl transferase (COMT) genotype and may be accompanied by corresponding brain alterations. To preliminary investigate and test our hypothesis in an artificially controlled pilot study. We enrolled 42 H-AVHs as subjects and used MRI and genetic methods to explore the basis brain features and the effect of dopamine antagonist treatment on AVHs in H-AVHs influenced by their COMT genotype or not.We found that COMT-met genotype subjects’ treatment response was better than that of COMT-val subjects. COMT-met genotype subjects demonstrated an increase in global functional connectivity density (gFCD) but no difference on gray matter volume (GMV) compared to COMT-val genotype subjects at baseline. More importantly, we found that after treatment, both groups demonstrated gFCD and GMV reduction, but the reduction was more widespread in COMT-met genotype subjects than in COMT-val genotype subjects.This study is the first to report that H-AVH subjects’ baseline brain functional features are influenced by their COMT genotypes and that the COMT-met genotype subjects exhibited better responses to dopamine antagonists but had more widespread GMV and gFCD reduction than subjects with the COMT-val genotype. Despite several limitations, these findings may provide auxiliary information to further explain the mechanisms of AVHs and provide a clue for scholars to further explore specific treatment targets for AVHs in H-AVH subjects or in schizophrenia patients.